PHYTATE ACTIVITY OF THERMOPHILIC BACTERIA FROM SULILI HOT SPRINGS IN PINRANG DISTRICT SOUTH SULAWESI - Hafsan Hafsan; Nurjannah Nurjannah; Cut Muthiadin; Isna Rasdianah Aziz; Ahyar Ahmad; Laily Agustina; Asmuddin Nasir (Scripta Biologica, 2018)
This study aimed to determine the optimum temperature and pH of the phytase activity produced by isolate of thermophilic bacteria from Sulili hot springs in the district Pinrang south sulawesi. This is a descriptive research, that measure of phytase activity by treated the variation of temperature and pH. The various of temperature has eight levels ie 20; 30; 40; 50; 60; 70; 80; and 90oC, the pH treatments consists of eight levels ie 2; 3; 4; 5; 6; 7; 8 and 9. Phytase activity was determined by converting the Na-phytate absorbance values produced by phytase enzyme against Na-phytate standard curve. One unit of phytate enzyme activity is defined as the amount of enzyme capable of hydrolysed Na-phytate and produce a peptide which is equivalent to one mole of tyrosine per minute under the conditions of analysis. The results of studies have shown that there is a significant effect of temperature on the phytase activity of Bacillus coagulans, thermophilic bacteria from Sulili hot springs, whereas no significant effect of pH treatment. Optimum phytase activity of B. coagulans are at 60°C and pH 7 ie 6.11 units/ mL.